An Approach to Identity Theft Detection Using Social Network Analysis - Kolaczek, G. (2009 First Asian Conference on Intelligent Information and Database Systems : 1-3 April 2009, 2009)
The paper presents a method of automatic detection of identity theft related event. The method is based on the social network analysis. The protection of electronic identity in contemporary information society is one of the greatest challenges in security research. The main idea about method of identity theft detection described in the paper is that identity theft events are related to change of the subject's behavior as the node of the social network (or several different networks). In consequence identity theft may be detected similarly as the other types of malicious activities by analyzing the change of observed behavior patterns.